Values, Cities and Migrations Real Estate Market and Social System in a Multi-cultural City - Napoli, Grazia; Mondini, Giulio; Oppio, Alessandra; Rosato, Paolo; Barbaro, Simona (Green Energy and Technology, 2023)
XI, 255 p. 78 illus., 72 illus. in color.